Theoretical biochemistry : processes and proterties of biological systems (Theoretical and computational chemistry, 2001)
Theoretical chemistry has been an area of tremendous expansion and development over the past decade; from an approach where we were able to treat only a few atoms quantum mechanically or make fairly crude molecular dynamics simulations, into a discipline with an accuracy and predictive power that has rendered it an essential complementary tool to experiment in basically all areas of science. This volume gives a flavour of the types of problems in biochemistry that theoretical calculations can solve at present, and illustrates the tremendous predictive power these approaches possess. A wide range of computational approaches, from classical MD and Monte Carlo methods, via semi-empirical and DFT approaches on isolated model systems, to Car-Parinello QM-MD and novel hybrid QM/MM studies are covered. The systems investigated also cover a broad range; from membrane-bound proteins to various types of enzymatic reactions as well as inhibitor studies, cofactor properties, solvent effects, transcription and radiation damage to DNA.